Differences in the level of basic and specific motor abilities of basketball players with respect to their position in the team - Ceremidzic, D.; Ceremidzic, T.; Perovic, T.; Bjelica, B. (XXI Scientific Conference "FIS COMMUNICATIONS 2018" in physical education, sport and recreation (Nis, Serbia, October 18-20, 2018), 2018)
The research was conducted with the aim to establish current level of motor abilities of basketball players currently selected in the cadet basketball team of Bosnia and Herzegovina, as well as differences between them with respect to their position in the team. Basketball players from the best clubs in the Republic of Srpska and Federation of Bosnia and Herzegovina took part in this research. Total number of participants is 16 selected players divided into two groups according to their position (inside or outside). Upon statistical data processing research results suggested that there are statistically significant differences in all the tested motor abilities between the two aforementioned groups of subjects.